Lake eutrophication in northeast China induced by the recession of the East Asian summer monsoon. (1st April 2022) - Chen, Lin; Zhao, Jiaju; Zhang, Zhiping; Shen, Zhongwei; Dong, Weimiao; Ma, Rui; Chen, Jie; Niu, Lili; Chen, Shengqian; Wu, Duo; Liu, Jianbao; Zhou, Aifeng
Abstract: Lakes are one of the most important freshwater resources on Earth and they provide a wide range of ecosystem services. However, due to rapid economic development and the intensification of human activities, many lakes have become eutrophic, which may threaten their status as water resources. Human activities have played a significant role in lake eutrophication, but whether this role is independent of, or coupled with, natural climate change requires further study. We selected Dali Lake, a large lake affected by human activity within the ancient warfare borders, to clarify the ecological response of a lake to climate change and human activity. We used analyses of sedimentary n -alkanes and AMS 14 C dating to reconstruct the paleolimnological evolution of Dali Lake since 15 cal kyr BP, and specifically to assess the timing and causes of eutrophication. The results show that the short-chain n -alkanes (C17–19 -alkanes) in Dali Lake are mainly produced by bacteria and algae within the lake, and that the sedimentary absolute abundance of short-chain n -alkanes (A17–19 -alkanes) can be used as a proxy for assessing the ecological status of the lake. The ecological status of Dali Lake was the most stable during the early to middle Holocene, when the East Asian summer monsoon was strong, but bacterial and algal outbreaks occurred during three episodes of a weakened summer monsoon—the Older Dryas, Younger Dryas, and the Common Era—when the lake experienced different degrees of eutrophication. During the recession of the East Asian summer monsoon, the weakening of precipitation recharge of the lake led to a reduction in lake area and an increase in nutrient concentrations in the lake water, while aeolian dust input was an additional nutrient source, leading to bacterial and algal outbreaks. During the Common Era, lake eutrophication occurred in the context of both summer monsoon recession and enhanced human activities, but their combined effects did not lead to more intense lake eutrophication than was caused by monsoon recession during the Younger Dryas. We conclude that, although human activities have enhanced the eutrophication of Dali Lake, the reduction in lake size due to monsoon recession and the resulting increase in the salinity and nutrient concentration of the lake water, combined with increased aeolian inputs, were a more important trigger of lake eutrophication. Highlights: n -alkanes can be used to reconstruct changes in lake ecology. Lake eutrophication occurred following deglaciation and monsoon enhancement. Younger Drays summer monsoon weakening caused stronger lake eutrophication than has occurred in the past 2000 years. Increased human activity was not the only cause of lake eutrophication.